2015
DOI: 10.1016/j.erss.2015.08.026
|View full text |Cite
|
Sign up to set email alerts
|

Ambivalence, designing users and user imaginaries in the European smart grid: Insights from an interdisciplinary demonstration project

Abstract: As the smart grid is gradually implemented, there is an increased concern amongst researchers and policymakers for the role of users in such systems. For the smart grid to perform as expected, users must change. One approach to the relationship between users and technology proposes that success is more likely if users are involved in the design and development of technologies. This, however, is no small task. This article reports on a research project that set out to engage users through inviting them to parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 81 publications
(38 citation statements)
references
References 42 publications
0
37
0
1
Order By: Relevance
“…The key focus here has been on how market energy is produced by experts via distinctive knowledge, modelling tools, and many other tools besides. Partially, the energy market and its participants may be performed by overarching economic promises and visions (Pollock & Williams 2010): for example, imaginations about users of 'smarter' market-based electricity grids (Skjølsvold & Lindkvist 2015) or about ways of living in future low-carbon houses (Cherry et al 2017) can shape future policies, design, and development choices.…”
Section: Knowledge and Expertise Of The Energy Marketsmentioning
confidence: 99%
See 1 more Smart Citation
“…The key focus here has been on how market energy is produced by experts via distinctive knowledge, modelling tools, and many other tools besides. Partially, the energy market and its participants may be performed by overarching economic promises and visions (Pollock & Williams 2010): for example, imaginations about users of 'smarter' market-based electricity grids (Skjølsvold & Lindkvist 2015) or about ways of living in future low-carbon houses (Cherry et al 2017) can shape future policies, design, and development choices.…”
Section: Knowledge and Expertise Of The Energy Marketsmentioning
confidence: 99%
“…Where many studies hence use economics tools across different aspects of energy, much fewer have developed social studies of markets types of questions: concerning how knowledge about energy markets and their participants may bring about these subjects rather than merely describing them (for key exceptions see Cointe 2015;Skjølsvold & Lindkvist 2015;Cherry et al 2017). Furthermore, in disciplinary terms, sociology, anthropology, and STS remain relatively minor points of departures in energy social research, but have unique insights in rethinking the relationship between energy, economics, and performativity.…”
Section: Introductionmentioning
confidence: 99%
“…However, this is dependent on how experiments and tests are carried out in practice, and they will always involve a certain level of framing and bias. Skjølsvold & Lindkvist (2015) showed how intentions of user-centred design and user participation in a European smart grid demonstration project were in practice overshadowed by the technology developers' images of the users. Similarly, Abi Ghanem & Mander (2014) through another European smart grid project identified that it is the expectations of project engineers and designers of future household users as economic rational consumers that structure technological design and household experiments.…”
Section: Users Scripts and Experimental Projectsmentioning
confidence: 99%
“…Som en av våre informanter sa: «[forbrukerne] må ha informasjon, og de må få opplaering og informasjon, tror jeg, før de gjør noe som helst» (Ekspert 1). Denne fortolkningen av brukerne som preget av et kunnskapsunderskudd, er også identifisert i mange tidligere studier av teknologiutvikling på dette feltet (Skjølsvold & Lindkvist, 2015;Throndsen & Ryghaug, 2015).…”
Section: Forventninger Til Brukerne I Produksjonen Av Fleksibilitetunclassified